After the Crime: Rewarding Offenders’ Positive Post-Offense Conduct - Robinson, Paul H. (2021)
While an offender’s conduct before and during the crime is the traditional focus of criminal law and sentencing rules, an examination of post-offense conduct can also be important in promoting criminal justice goals. After the crime, different offenders make different choices and have different experiences, and those differences can suggest appropriately different treatment by judges, correctional officials, probation and parole supervisors, and other decision-makers in the criminal justice system.Positive post-offense conduct ought to be acknowledged and rewarded, not only to encourage it but also as a matter of fair and just treatment. This essay describes four kinds of positive post-offense conduct that merit special recognition and preferential treatment: the responsible offender, who avoids further deceit and damage to others during the process leading to conviction, the debt-paid offender, who suffers the full punishment deserved (according to true principles of justice rather than the sentence actually imposed), the reformed offender, who takes affirmative steps to leave criminality behind, and the redeemed offender, who out of genuine remorse tries to atone for the offense.The essay considers how one might operationalize a system for giving special accommodation to such offenders. Positive post-offense conduct might be rewarded, for example, through the selection and shaping of sanctioning methods, through giving preference in access to education, training, treatment, and other programs, and through elimination or restriction of collateral consequences of conviction that continue after the sentence is completed